Ally McBeal : Season 2 Episodes : 13-16 - Dugan, Dennis, 1946-; Calista, Flockhart (USA 20th Century Fox Television, 1998)
Ally McBeal and Billy Thomas were going steady throughout their childhoods. Ally even followed Billy to Harvard law school despite having no interest in law. But when Billy chose to pursue a career in law away from Ally, their relationship came to an end. In the present, an old classmate of Ally's named Richard Fish gives Ally a job at his law firm, where Billy and his new wife are also working. This puts Ally in a predicament since she still has feelings for Billy which she's laboring to get over. At the office, Ally puts up with a nosy, gossiping secretary named Elaine, and an oddball lawyer named John Cage never seems to lose a case. At home, Ally's friend and house-mate Renée regularly advises her on her love life. The series follows Ally's trials and tribulations in life through her eyes, and caricaturizes her personal thoughts and fantasies.
Ally McBeal is a single young lawyer looking for love and fullfillment in life. She works for a Boston Law firm with her ex-lover and his wife, a money loving boss and an annoying receptionist. With all that is going on she must contend with her feelings and her over active imagination.
Keywords: Comedy; Drama; Music -- Instruction and study; Romance